Utilisation of Acoli Folktales for Mindset Modification in Post-LRA Incursions: A Sociological Perspective - Ocan, Johnson; Okumu, Charles (Southern African Journal of Folklore Studies, 2025)
This study explores the sceptre of Acoli folktales on mentality adjustment among the Acoli people of northern Uganda. The overarching terminus of the study was to analyse the implications of Acoli folktales in mentality adjustment in the post-Lord Resistance Army (LRA) infringements in Acoli land. This was accomplished by conducting a literature review of some selected Acoli folktales, with a quintessence on the underlying concepts such as deceit, boredom, boastfulness, rebellious-ness, and treachery. Like any other traditional edification, the traditional Acoli community has pre-served group cohesiveness and unconscious acceptance of customary codes articulated, and en-coded in 13 their oral narratives (myths, legends, and folktales) to ensure a peaceful life in the ge-nealogy and community. The study found that folktales have momentousness in kinfolk regulation. Furthermore, the study claims that a commune with a strong awareness of folktales and their impli-cations for mentality adjustment would view squabbles as an integral aspect of human existence and harmonious living and would hence avoid actions and inactions 19 that foster antipathy.